SISTEM PAKAR DIAGNOSIS AWAL PENYAKIT MALARIA TERHADAP MANUSIA MENGGUNAKAN METODE DEMSPTER SHAFER THEORY - Marselinus Nick Aliandu; Yustina Rada; Desy A. Sitaniapessy (Nindikayla Institute, 2023)
Malaria is a parasitic infectious disease caused by plasmodium inside erythrocytes. Along with the development of technology, the diagnosis of malaria can be done through a technological system, namely an expert system that makes it easier to conduct initial examinations. In East Sumba district, malaria is caused by geographical conditions such as settlements far from hospitals / medical personnel and other causes, namely patients still do not understand the prevention, symptoms, and complications of malaria infection and lack of adherence to taking drugs. This research aims to develop an expert system to diagnose malaria. Through this system, it is expected to facilitate decision making to determine the type of malaria in patients who seek treatment at health care facilities. This diagnostic expert system is developed based on symptoms obtained from experts, namely health experts. This expert assessment aims to strengthen the theory and decision-making results that will be taken by this system. This research is a development research with the Dempster Shafer method. This research data was collected using interviews, observations, and literature studies. This system development method includes the stages of software requirements analysis, software design, and expert system design. The end result of developing this system is to produce an expert system in the early diagnosis of malaria